Development and application of an analytical method for curdione quantification in pregnant sprague–dawley rats by LC‐MS/MS. (4th March 2015) - Meng, Xiang; Zhang, Ting; Li, Ying; Pan, Qi; Jiang, Juan; Luo, Yongwei; Chong, Liming; Yang, Yang; Xu, Sichong; Zhou, Li; Sun, Zuyue
Abstract The vaginal administration route suffers from relatively low absorption efficiency, which may hinder the identification of the toxicokinetics of curdione in pregnant women. A sensitive analytical method for determining the plasma concentration of curdione was developed and applied in the determination of curdione in pregnant Sprague–Dawley rats as a simulated model. Glimepiride was used as an internal standard and chromatographic separation was achieved on a Capcell Pak C18 MGIII column. A gradient elution profile with 0.5% formic acid (A)–0.5% formic acid–acetonitrile (B) was selected as mobile phase. The selected reaction monitoring mode was used for quantification based on the target fragment ions m/z 237.2 to m/z 135.1 for curdione and m/z 491.3 to m/z 352.1 for the glimepiride. The standard curve was linear over the range of 0.5–500 ng/mL for curdione in rat plasma and yielded a consistent peak pattern, even at the lower limit of quantitation of 0.5 ng/mL. The retention times of curdione and IS were 6.55 and 6.59 min, respectively. The mean recovery of curdione in rat plasma was 95.5–101.1%. The intra‐day and inter‐day precisions were between 2.35 and 9.08%. This LC‐MS/MS method provides a simple and sensitive means for determining the plasma concentration. Copyright © 2015 John Wiley & Sons, Ltd.